Investigation of the Influence of Nanostructured LiNi0.33Co0.33Mn0.33O2 Lithium-Ion Battery Electrodes on Performance and Aging. Issue 2 (1st January 2018) - Dreizler, Andreas M.; Bohn, Nicole; Geßwein, Holger; Müller, Marcus; Binder, Joachim R.; Wagner, Norbert; Friedrich, K. Andreas
Abstract : The paper focuses on the performance and aging behavior of lithium nickel cobalt manganese oxide commercial standard material (NCM-111) which is improved with a post synthesis process in order to enhance the cathode active material of lithium-ion pouch cells regarding their capacity and cyclic stability. The aging behavior of the cells is analyzed with electrochemical impedance spectroscopy (EIS) during long-term electrochemical load cycling tests based on the Common Artemis Driving Cycle (CADC). Additionally, post-mortem investigations using scanning electron microscopy (SEM) and X-ray diffraction (XRD) were performed. The results demonstrate that post-processing of electrode active material is an effective tool to improve the properties of lithium-ion electrode materials, especially regarding high energy applications and lifetime optimization. The paper bridges the gap between lithium-ion battery electrode material development and the necessary cell testing under automotive relevant conditions which is important for the evaluation of new lithium-ion battery materials for automotive applications.